Develop a new Student Attendance system Using QR Code for Smartphone - A. Khalid, Noor Aldeen (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The student attendance system serves as a means to assess student engagement in a classroom setting. As universities transition from online to in-person lectures, they grapple with challenges associated with managing large student populations, notably the cumbersome task of recording attendance for performance evaluation. This process not only consumes valuable lecture time but may also be susceptible to errors and classroom disturbances. In response to these challenges, this paper introduces an attendance system using QR codes on smartphones based on PC. Each student is assigned a unique QR code, enabling them to mark their attendance using their phones, eliminating the need for an internet connection. Implementing this system offers the dual advantage of time efficiency in attendance tracking and the integration of technology to replace the conventional method of verbally calling out each student's name or asking them to write. The design of this proposed system leverages technologies such as OpenCV through Python, along Visual C++ Redistributable Packages for Visual Studio.